2011
DOI: 10.3344/kjp.2011.24.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Catheter Malposition in a Failed Epidural Anesthesia Confirmed by Computed Tomography

Abstract: We report a case of failed epidural anesthesia despite successful identification of the epidural space, loss of resistance technique, hanging drop method and drip infusion. This case evaluated the use of computed tomography to confirm epidural catheter position, which showed the catheter accidentally positioned at the T2 lamina. Because epidural anesthesia can even after successful procedure using standardized techniques such as loss of resistance, we recommend performing the procedure under fluoroscopic guida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Similarly, adverse effects and complications associated with epidural analgesia may be influenced by a number of factors, including epidural catheterization technique, use of intrathecal route and choice of local anesthetic agent and opioid [19][20]. Breakthrough pain after receiving pain relief can increase patient dissatisfaction and may induce fear and worsen anticipatory pain [21].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, adverse effects and complications associated with epidural analgesia may be influenced by a number of factors, including epidural catheterization technique, use of intrathecal route and choice of local anesthetic agent and opioid [19][20]. Breakthrough pain after receiving pain relief can increase patient dissatisfaction and may induce fear and worsen anticipatory pain [21].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, although we excluded cases in which the enhanced epidural space was not included in the imaging field of view, cases in which contrast enhancement was not detected because too much time had passed after injection, and cases that could not be evaluated for unknown reasons, it is possible that abnormal findings, such as enhanced subdural space [ 39 – 47 ] and enhanced subarachnoid space [ 24 , 48 ], might not have been diagnosed sufficiently. Although there have been reports of the usefulness of lateral radiography [ 2 , 3 , 49 ] and computed tomography [ 6 , 36 , 50 , 51 ] for the evaluation of contrast enhancement in the epidural space, these imaging studies may be less practical in daily clinical practice because of issues regarding medical costs and procedural simplicity. The present study showed that deviation of an epidural catheter from the epidural space could sufficiently be assessed only with frontal plain abdominal radiographs and that plain abdominal radiography is a simple and useful method to improve the postoperative analgesic effect of epidural anesthesia.…”
Section: Discussionmentioning
confidence: 99%